Three new species of genus Apotropina Hendel from China (Diptera, Chloropidae) - Liu, Xiaoyan; Yang, Ding (Zootaxa, 2015)
A review of the species of the genus Apotropina Hendel from China is provided. The following 3 species are described as new to science: A. bistriata sp. nov., A. longiprocessa sp. nov. and A. tristriata sp. nov. A key to all species of Apotropina from the Oriental Region is given.